PENGARUH PROFITABILITAS, LIKUIDITAS, DAN LEVERAGE TERHADAP FINANCIAL DISTRESS - Ni Made Nita Saputri; Kadek Dewi Padnyawati (UNHI Press, 2021)
This study aims to obtain empirical evidence regarding the effect of profitability, liquidity, and leverage on financial distress (a case study of property and real estate sector companies listed on the Indonesian stock exchange for the period 2017 - 2019). The sample selection technique in this study was purposive sampling and obtained a sample size of 26 companies with 78 observations. The data analysis technique in this research is logistic regression analysis technique.The results of the research analysis show that the profitability variable has a positive regression coefficient of 0.109 with a significance value of 0.982> 0.05 so that the profitability variable has a positive and insignificant effect on financial distress. The liquidity variable has a negative coefficient of -0.048 with a significance value of 0.145> 0.05 so that the liquidity variable has a negative and insignificant effect on financial distress. The leverage variable has a negative coefficient of -653 with a significance value of 0.177> 0.05, so the leverage variable has a negative and insignificant effect on financial distress.